Research on Calculation Method of Hydraulic Damper Dynamic Characteristics - ZHOU Xiaozhi; CHI Maoru; GAO Hongxing; YANG Dongxiao; QIN Jiansheng (机车电传动)
Based on the Maxwell model calculation method of hydraulic damper dynamic characteristics, the calculation method of the dynamic characteristics of the hydraulic damper was improved by theoretical analysis, with the bench test, the improved algorithm was compared with the existing calculation standard, and the correctness of the improved method was verified. The results showed that, the calculation results are consistent for the bidirectional flow hydraulic damper, which the F-s indicator diagram is nearly symmetry; there are some differences between the two computational results for the unidirectional flow hydraulic damper, which are shown to be asymmetrical F-s indicator diagram. The improved algorithm is a universal method for calculating the dynamic characteristics of hydraulic damper.